Inter Provincial Youth Human Capital Mapping and Its Implications for Economic Growth Policy in Indonesia - Qorinul Huda (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2026)
Youth are a strategic national asset because they are of productive age, determining the direction of future economic development. This study is based on the hypothesis that the quality of youth human capital influences economic growth across provinces in Indonesia. Data are sourced from the Central Statistics Agency (BPS) in 2024, with 38 provinces as analysis units. The methods used include biplot analysis to map variations in youth human capital indicators (education, health, and employment) and multiple linear regression to examine their influence on per capita economic growth. The results show disparities in youth human capital across provinces, with Java and parts of Sumatra being relatively superior compared to eastern Indonesia. Health and employment factors have been shown to influence economic growth, while education shows a contradictory relationship due to the phenomena of skill mismatch and time lag. These findings confirm that human development, especially youth development, is a crucial foundation for achieving the 2025–2045 RPJPN targets towards an Advanced Indonesia. Mapping human capital potential allows for targeted local-scale policy mapping.